The Right to Withdraw as a Mechanism for Protecting the Satisfaction of the Electronic Consumer - Mohammed Reda Azrou (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
The electronic consumer usually purchases goods and services online from professionals or specialists and then discovers that these products or services do not match the description displayed on the website. This happens due to misleading advertising and quick contracting without sufficient thought. For this reason, the Algerian legislators and comparative legislations have recognized the consumer's right to withdraw from the electronic contract without any compensation.